2009
DOI: 10.1037/a0014252
|View full text |Cite
|
Sign up to set email alerts
|

Combining simultaneous with temporal masking.

Abstract: Simultaneous and temporal masking are two frequently used techniques in psychology and vision science. While there are many studies and theories related to each masking technique, there are no systematic investigations of their mutual relationship, even though both techniques are often applied together. Here, we show that temporal masking can both undo and enhance the deteriorating effects of simultaneous masking depending on the stimulus onset asynchrony between the simultaneous and temporal mask. For the tas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 74 publications
2
6
0
1
Order By: Relevance
“…In foveal vision, we found also that pattern completion, another grouping cue, determines crowding (Hermens et al, 2009). Here we first showed that our foveal results also hold true in peripheral vision.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…In foveal vision, we found also that pattern completion, another grouping cue, determines crowding (Hermens et al, 2009). Here we first showed that our foveal results also hold true in peripheral vision.…”
Section: Discussionsupporting
confidence: 71%
“…We determined offset discrimination thresholds for a vertical vernier. Compared to the stimuli presented by Hermens et al (2009), we increased the size of the vernier by a factor of 4 to adapt for peripheral vision. The vernier was composed of two vertical lines 40 0 (arcmin) long separated by a vertical gap of 4 0 .…”
Section: Apparatus and Stimulimentioning
confidence: 99%
See 1 more Smart Citation
“…, 2005, 2007a, 2009; Hermens & Ernst, 2007; Hermens & Herzog, 2007; Herzog, 2007; Herzog et al. , 2007; Hermens et al. , 2009a,b).…”
Section: Discussionunclassified
“…In fact, there are other reported instances of masking aiding perception, but these tend to be in fairly specialized circumstances, often when the mask stimulus combines with the target stimulus in a constructive way. One such situation is near-threshold pedestal detection (Nachmias & Sansbury, 1974;Swift & Smith, 1984), and another involves vernier offset discrimination (Hermens, Herzog, & Francis, 2009). However, in the present instance, integration is facilitated and performance improved precisely because masking is effective for reducing the visual-system response to the second set of stimuli.…”
Section: Discussionmentioning
confidence: 66%